2022
DOI: 10.3389/fnsys.2022.765720
|View full text |Cite|
|
Sign up to set email alerts
|

Electrophysiological Markers of Fairness and Selfishness Revealed by a Combination of Dictator and Ultimatum Games

Abstract: Individual behavior during financial decision making is motivated by fairness, but an unanswered question from previous studies is whether particular patterns of brain activity correspond to different profiles of fairness. Event Related Potentials (ERPs) were recorded from 39 participants who played the role of allocators in a Dictator Game (DG) and responders in an Ultimatum Game (UG). Two very homogeneous groups were formed by fair and selfish individuals. At fronto-central cortical sites, the latency of ERP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 163 publications
(202 reference statements)
0
5
0
Order By: Relevance
“…Previous studies proposed that certain brain dynamics could be linked to moral decisions ( Xu et al, 2020 ; Miraghaie et al, 2022 ). Among studies that adopted the DG paradigm, Miraghaie et al (2022) noted an unresolved question concerning whether specific patterns of brain activity correlate with different profiles of fairness. This question prompted the researchers to conduct an experiment that delved deeper into the topic.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies proposed that certain brain dynamics could be linked to moral decisions ( Xu et al, 2020 ; Miraghaie et al, 2022 ). Among studies that adopted the DG paradigm, Miraghaie et al (2022) noted an unresolved question concerning whether specific patterns of brain activity correlate with different profiles of fairness. This question prompted the researchers to conduct an experiment that delved deeper into the topic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This question prompted the researchers to conduct an experiment that delved deeper into the topic. In their study, Miraghaie et al (2022) used event-related potentials (ERPs) and randomly divided 39 participants into two groups (fair or selfish). All participants assumed the role of allocators in a DG.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been related to negative cognitive biases and hypersensitivity to aversive events. However, others studies have observed a diminished MFN effect (difference between task conditions) in depression and anxiety, possibly linked to a negative bias in outcome expectation (Foti & Hajcak, 2009;Gu et al, 2010;Miraghaie et al, 2022). Finally, studies have also reported decreased MFN amplitudes in MD during positive stimuli, related to dysfunctional reward processing (Brush et al, 2018;Foti & Hajcak, 2009;Liu et al, 2014;Weiß, Rodrigues, et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…We had no specific hypothesis regarding group differences on MFN during negative stimuli (i.e. mid‐value and unfair offers), since both an enhanced negative response (Judah et al, 2016; Mueller et al, 2015; Santesso et al, 2008; Tucker et al, 2003) as well as a blunted negative response due to bias negative expectation (Foti & Hajcak, 2009; Gu et al, 2010; Miraghaie et al, 2022) could be expected in MD and SA. Finally, we expected decreases in P3/LPP in the MD/SA group, as motivation deficits and negative cognitive biases (which could compete in resources with the P300; Barron et al, 2011; Smallwood et al, 2008) were likely to take place during a social task such as the UG.…”
Section: Introductionmentioning
confidence: 99%